A nematode effector inhibits plant immunity by preventing cytosolic free Ca2+ rise. (4th August 2022) - Guo, Bin; Lin, Borong; Huang, Qiuling; Li, Zhiwen; Zhuo, Kan; Liao, Jinling
Abstract: The Meloidogyne enterolobii effector MeTCTP is a member of the translationally controlled tumour protein (TCTP) family, involved in M. enterolobii parasitism. In this study, we found that MeTCTP forms homodimers and, in this form, binds calcium ions (Ca 2+ ). At the same time, Ca 2+ could induce homodimerization of MeTCTP. We further identified that MeTCTP inhibits the increase of cytosolic free Ca 2+ concentration ([Ca 2+ ]cyt ) in plant cells and suppresses plant immune responses. This includes suppression of reactive oxygen species burst and cell necrosis, further promoting M. enterolobii parasitism. Our results have elucidated that the effector MeTCTP can directly target Ca 2+ by its homodimeric form and prevent [Ca 2+ ]cyt rise in plant roots, revealing a novel mechanism utilized by plant pathogens to suppress plant immunity. SUMMARY STATEMENT: The Meloidogyne enterolobii effector MeTCTP directly binds Ca 2+, probably by its homodimeric form, and prevents cytosolic free Ca 2+ concentration rises in plant roots, leading to the suppression of host innate immunity including reactive oxygen species burst and cell necrosis.